2018
DOI: 10.1038/s41598-018-27662-0
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 and p38 regulate inter-individual variability in ozone-mediated IL-8 gene expression in primary human bronchial epithelial cells

Abstract: Inter-individual variability is observed in all biological responses; however this variability is difficult to model and its underlying mechanisms are often poorly understood. This issue currently impedes understanding the health effects of the air pollutant ozone. Ozone produces pulmonary inflammation that is highly variable between individuals; but reproducible within a single individual, indicating undefined susceptibility factors. Studying inter-individual variability is difficult with common experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…An explanation for the ceiling effect could be due to the "shunting" effect when p38 inhibitors are utilized in this assay system at the level of MAPK phosphorylation. This cross-talk or shunting between the ERK and p38 pathways have been previously reported in osteosarcoma cells, 47 PC12 cells, 48 bronchial epithelial cells 49 and in corneal epithelial cells. 50 In corneal epithelial cells and osteosarcoma cells, it was reported that inhibition of either one of the MAPK pathways could result in the activation of the other.…”
Section: Discussionsupporting
confidence: 76%
“…An explanation for the ceiling effect could be due to the "shunting" effect when p38 inhibitors are utilized in this assay system at the level of MAPK phosphorylation. This cross-talk or shunting between the ERK and p38 pathways have been previously reported in osteosarcoma cells, 47 PC12 cells, 48 bronchial epithelial cells 49 and in corneal epithelial cells. 50 In corneal epithelial cells and osteosarcoma cells, it was reported that inhibition of either one of the MAPK pathways could result in the activation of the other.…”
Section: Discussionsupporting
confidence: 76%
“…Our observations are aligned with those of previous studies using ALI lung models, showing preserved responses to certain stimuli across donors despite variations in intensity. For instance, the secretion profile of proinflammatory mediators ( Banerjee et al, 2017 ) and the changes in gene expression in response to cigarette smoke exposure ( Haswell et al, 2017 ; Iskandar et al, 2017b ) as well as the inflammatory response following ozone exposure ( Bowers et al, 2018 ) followed similar patterns across cultures from different donors, although they varied in magnitude. In contrast, the inflammatory response of airway cultures to influenza virus infection seems to be more impacted by the donor of the cultures ( Ilyushina et al, 2019 ), which suggests that interdonor variability should be specifically addressed for each endpoint and experimental condition tested.…”
Section: Discussionmentioning
confidence: 99%
“…Cells and EVs were lysed in RIPA buffer and subjected to Western blotting as previously described [ 36 ], with modifications as noted for ORF2p. Immunoblots were imaged using a Konica Minolta SRX101A film developer and the Licor Odyssey FC Imaging System (LI-COR Biosciences, Lincoln, Nebraska, USA).…”
Section: Methodsmentioning
confidence: 99%